HUBUNGAN LAMA PAPARAN INHALASI ORGANICSOLVENT TERHADAP PENURUNAN PENGLIHATAN WARNA DAN SENSITIVITAS KONTRAS - husnaini husnaini; Getry Sukmawati; Andrini Ariesti (Universitas Fort De Kock, 2020)
Chronic inhalation of organic solvents causes retinal toxicity such as decreased color vision and contrast sensitivity because organic solvents cause damage to photoreceptor function, changes in cortical or retinal neurotransmitter systems such as glutamate, dopamine and acetylcholine and changes in function in parvo, magno and coniocellular cells. Method: The sample of this study consisted of 45 gas station operators who were divided into 3 groups, namely those who worked 1 year-5 years, 5 years-10 years and >10 years. All subjects underwent quantitative color vision examination by calculating the value of the color confusion index (CCI) using Fansworth D15. Contrast sensitivity examination is by determining the log contrast sensitivity value using the Pelli-Robson test. Results: CCI values> 1.00 and log contrast sensitivity values <1.65 were found in officers who worked for >10 years by 12 subjects (80%). Statistically there is a significant relationship between the duration of work with the decrease in color vision and contrast sensitivity (P Value 0,000). Conclusion: There is a significant relationship between the duration of exposure to organic solvents with a decrease in color vision and contrast sensitivity in operator officers who work >10 years.